Hybrid PRoPHET-Epidemic Routing Protocol for Optimizing Possibility of Sending Messages in Remote Fishermen Residential Area - Ariwibisono, F.X.; Basuki, Achmad; Ramdani, Fatwa (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Limitations of communications facilities and infrastructure in the residential areas of the fishermen create problems of information difficulty. Lack of signal availability from the nearest Base Transceiver Station (BTS) that can reach the fishermen's residential area. A solution is needed that allows the communication path from the residential area of the fishermen to the area available for communication facilities and infrastructure. From this issue, there are several methods that can be used to overcome this problem. One of the methods that are used as a solution is Delay or Disruption Tolerant Network (DTN) network architecture, and another method utilize Crowdsource Mobile Access (CrowdMAC) to send message data packets to the destination device. In this paper, we carried out the integration of PRoPHET and Epidemic routing protocols to increase the level of the possibility of sending packets via multiple nodes with crowdsourcing.